PERSPECTIVES OF TEACHERS ONLINE AND PRACTICAL KNOWLEDGE IN COVID -19 PANDEMIC ERA - Sri Wahyuni (Jurnal Bahasa Lingua Scientia, 2021)
Exploration of task preparation for teaching learning process TLP on online for educational time by the time remains high agenda for seeking new ways and means to improve the TLP. This is the challenges for the teacher to be presented in the implementation of teacher education programme that is convenient for the learners in TLP, as solution to the challenges in Education System in the era digital. Teachers prepare role of implementation step by step to learn and practice the necessary knowledge skills and attitudes to become teachers’ competence in the education system. Hopefully they are able to channel information to others for digital online. This research based on the covid-19 pandemic Era, that all activieties have done from home ( WFH), teachers must be proactive individually to expand their skill and join mentoring, training and briefing technical also seminar/workshop online for their ability in a pedagogical social, attitude, and professionalism. There are merits and demerits classes conducted via zoom and Google Classroom in TLP. Where as anything can be accomplished in the traditional classroom done electronically, information / material in TLP could be stored via technology but construction of knowledge especially a teacher cannot be replicated online. The aim of the study was examine the online media are applied in TLP for senior high school using zoom and google classroom as a medium, It also explored their beliefs about merits and demerits and investigated their practical knowledge do the teachers use, for meaningfulness of classes conducted via zoom on TLP in Covid -19 pandemic era as opposed to face to face classes. Qualitative data were collated and analyzed using descriptive statistics to . The conclusion were that zoom and google classroom classes were satisfying and convenient for teachers and others perceived them a litle resistance, and for the students 66,7 % like daring and 33,3 % didn’t like daring .